Clinical Procedures for Safer Patient Care - Doyle, Glynda Rees; McCutcheon, Jodie (Open textbook library., 2015)
The checklist approach, used in this textbook, aims to provide standardized processes for clinical skills and to help nursing schools and clinical practice partners keep procedural practice current. Each skill/procedure is covered in a chapter that has learning objectives, a brief overview of the relevant theory, checklists of steps for procedures with the rationale behind each step of the process, and a summary of key takeaways. Key terms are set in bold throughout the book and laid out again in a Glossary in the appendix. All 88 checklists are also summarized, and hyperlinked to the original checklist, in the appendix.